The Relationship between Parental Knowledge, Nutritional Status and Family Income with the Incidence of Stunting in Toddlers in the Pematang Johar Health Center Area - Telaumbanua, Mercy Gabriela; Pangaribuan, Mesrayani Delima; Gulo, Mersinar Talentagnes; Gaol, Yesinta Kristina Lbn; Sembiring, Meia Aprina; Nababan, Tiarnida (PT FORMOSA CENDEKIA GLOBAL, 2025)
Stunting remains a critical nutritional issue in Indonesia, affecting the growth and development of children. It results from various factors, including physiological, biochemical, and sociocultural elements, with inadequate nutrition being a key contributor. Mothers, as primary caregivers, play a crucial role in ensuring proper nutrition to prevent stunting, and a family's financial situation also influences the type and amount of food consumed. This study aimed to determine the relationship between stunting prevalence in toddlers in the Pematang Johar Health Center area with parental awareness, nutritional status, and household income. Using Slovin’s formula, 45 out of 50 participants were sampled. Chi-square and univariate analyses were applied. Results indicated significant associations with parental knowledge (p = 0.003), nutritional status (p = 0.043), and family income (p = 0.007).